MAKNA PERAYAAN PENGUCAPAN SYUKUR DI DESA BETELEN SATU KECAMATAN TOMBATU KABUPATEN MINAHASA TENGGARA - Tongotongo, Blevinsky; Rumampuk, Selvie; Mulianti, Titiek (Universitas Sam Ratulangi, 2021)
One of the cultures that is still carried out and maintained by the Minahasa community is the celebration of thanksgiving. In the tradition of thanksgiving there is Tonaas Wangko which regulates at the beginning of the growing season so that the harvest can be done and also often held foso (ritual). Tonaas Wangko also manages the time/day of thanksgiving celebrations. In the past people made thanksgiving on the grounds of giving thanks for the crops they get and in the past they celebrated with its meaning because the crops are abundant or not abundant, it is still they make because otherwise held people believe it will experience crop failure. As the day of thanksgiving begins to be determined by the government and the church, so that in the celebration of thanksgiving no longer coincides with the harvest season and also foso (ritual) is no longer held. The celebration of thanksgiving to the people of Betelen Satu Village, has meaning as a momentum of gratitude to God from the various livelihoods they get. They also consider this thanksgiving celebration as a 'baku dapa' event or meeting with family from afar in order to gather and express each other's joys and sorrows together so as to strengthen the brotherhood, even as a 'baku kenal' event or get acquainted with the first known person during the thanksgiving celebration.Keywords: meaning, celebration, thanksgiving